A Novel Study Design to Systematically Explore the Impact of Trial Methodology on Psychopharmacological Treatment Outcome in Patients with Depression - Severus, Emanuel; Sauer, Cathrin; Bauer, Michael; Ostacher, Michael; Anghelescu, Ion-George (Pharmacopsychiatry, 2019)
Introduction Randomized, double-blind, placebo-controlled trials were developed to draw rather unbiased conclusions regarding the efficacy of antidepressants in the treatment of a major depressive episode (internal validity), mostly with the purpose of formal approval of new compounds in this indication. However, at the same time, data suggest that the very process of randomization and blinded administrations of placebo will have a significant impact on the efficacy of the antidepressant tested and therefore may limit the external validity of results obtained from this type of studies. Therefore, there is an urgent need to systematically study the impact of randomization/placebo control/blinding on patient population, efficacy, tolerability, and external validity in the psychopharmacological treatment of patients with a major depressive episode.Methods To develop a study design that allows the systematic exploration of the impact of trial design on characteristics of included patient population and outcome.Results We propose a study design including sample size calculation and statistical analysis in which patients with a major depressive episode are randomized to 3 distinct study designs that differ with regard to control, randomization, and blindness.Discussion The results of the proposed study design may have substantial consequences when it comes to how to best interpret the results of traditional randomized, double-blind, placebo-controlled trials in the acute treatment of major depressive disorder. Furthermore, they may lead to the implementation of new study designs that may be more suitable for assessing the effectiveness of new antidepressant compounds in everyday clinical practice.
Keywords: antidepressant; random allocation; trial design; randomized controlled trials as topic; major depressive disorder